PSIKOLOGI GAME DAN VIRTUAL REALITY DALAM PERSPEKTIF SELF-DETERMINATION THEORY - Agung Perdana Putra; Masyhuri (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This article examines the psychology of digital games and virtual reality through the lens of Self-Determination Theory (SDT) developed by Edward Deci and Richard Ryan. The study explores four interrelated psychological phenomena: flow experience, immersion, gamification, and the perceptual effects of virtual reality. Flow refers to the state of complete concentration and enjoyment during gameplay when challenge and skill are balanced. Immersion describes the psychological state of being deeply absorbed in a digital environment. Gamification involves applying game elements to non-game contexts to enhance motivation and engagement. Virtual reality affects human perception by providing realistic three-dimensional sensory stimulation that alters spatial awareness and information processing. Using SDT as the grand theory, this paper argues that digital games and virtual reality are psychologically compelling because they fulfill three basic psychological needs: autonomy, competence, and relatedness. The analysis draws on studies from Indonesian universities and international research to contextualize these phenomena within the Indonesian educational and digital landscape. Findings suggest that these technologies offer significant potential for educational applications while also presenting challenges such as digital dependence and cybersickness. Balanced and informed use of digital technologies is recommended.